Spot morning urine protein creatinine ratio and 24 hour urinary total protein excretion rate - Rahman, MM; Azad, K; Ahmed, N.R.; Haque, MR; Wahab, MA; Asad, HB; Mollah, FH; Arslan, MI (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):146-9The abstract of this article is available on the PubMed website